Pengaruh jenis perekat terhadap kualitas biobriket hasil pirolisis limbah biomassa lignoselusa D07 - Restin, Restin; Ifa, La; Yani, Syamsuddin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Currently the world is facing energy crisis. This is due to the increasingly depleting energy sources from non-renewable fossil raw materials such as petroleum, natural gas and coal which are not balanced by increasing population growth. The solution to the energy crisis from fossil raw materials is using alternative energy sources, one of them is biomass. Lignocellulose D07 is a product biomass from the seaweed processing industries, that comes from plant lignocellulose. Biomass quality can be improved by using the pyrolysis method. Pyrolysis is a thermal degradation method without the oxygen. Pyrolysis produces two main products, that is char (charcoal) and liquid smoke. Pyrolysis temperature can affect the quality of the resulting product. Charcoal from the pyrolysis process can be used for making biobriquettes. Biobriquettes one of renewable energy that can be produced from various raw materials, are cleaner and environmentally friendly. When we make biobriquettes, we need add adhesive to unite the charcoal granules so that they can be shaped as needed. The type of adhesive can affect the quality of the product produced. Based this background, this research has two objectives, namely to determine the effect of pyrolysis temperature on the quality of charcoal and to determine the effect of adhesive type on the quality of briquettes. There are three pyrolysis temperatures used, namely 300,350,400⁰C, while the adhesive used includes starch, sago and cornstarch. The analysis carried out includes water content, ash content, volatile matter, heating value and sulfur. Based on the research results, it was found that a pyrolysis temperature of 400 ⁰C was the best variable with a water content of 2.8%, ash content of 5.2%, volatile content of 30.47 and a heating value of 6832 cal/gram. Meanwhile, the briquette adhesive that showed the best quality was obtained from sago with the highest calorific value of 6874 cal/gram, water content of 4.9%, ash content of 5.06% and volatile matter of 40.66%.